PERAN ORANG TUA DALAM MENDAMPINGI ANAK BELAJAR SELAMA MASA BELAJAR DARI RUMAH - Rudy Ntelok; Yustina Dewi Sartika Nantung; Marianus Mantovani Tapung (Program Studi Guru Sekolah Dasar (UNIKA Santu Paulus Ruteng), 2021)
The purpose of this research was to describe the role of parents in assisting of students studying during the period of studies from home, as well as to describe the constraints of parents to do that activity. This research used qualitative approach with library research method. Data were collected using documentation techniques and analyzed by adopting the data analysis model from Miles and Hubermann. The results showed that the role of parents in assisting of students studying during the period can be describe as 1) a teachers at home, where parents can guide and accompany children to study remotely from home, 2) as facilitator, 3) as motivators and 4) as influences or directors. However, there were several obstacles faced by parents in online learning like 1) lack of understanding of the material by parents, 2) do not have enough time to accompany children because they have to work., 3) parents are impatient in accompanying children while studying at home, 4) difficulty in operating gadgets, 5) unstable internet service coverage and 6) no electricity. The solution that can be done to maximize the role of parents is to learn to understand technology and consult with teachers regarding children's learning progress.